Island area and historical geomorphological dynamics shape multifaceted diversity of barrier island floras. Issue 8 (25th May 2022) - Ferreira‐Arruda, Thalita; Guerrero‐Ramírez, Nathaly R.; Denelle, Pierre; Weigelt, Patrick; Kleyer, Michael; Kreft, Holger
Abstract : The influence of island dynamics and characteristics on taxonomic diversity, particularly species richness, are well studied. Yet, our knowledge on the influence of island dynamics and characteristics on other facets of diversity, namely functional and phylogenetic diversity, is limited, constraining our understanding of assembly processes on islands (e.g. biogeographic history, dispersal and environmental filtering and species interactions). Using barrier islands, a highly dynamic and so far, understudied island type, we investigate how multiple facets of vascular plant diversity (functional, phylogenetic and taxonomic diversity) are shaped by island geomorphology, modern and historic area, and habitat heterogeneity. In line with our expectation, historical dynamics in island geomorphology affected phylogenetic and taxonomic diversity via habitat heterogeneity. However, island area was the best predictor across all facets of diversity. Specifically, larger islands had higher functional and phylogenetic diversity than expected by chance while most of the smaller islands had lower diversity. The influence of area on functional diversity acted via habitat heterogeneity, with habitat heterogeneity influencing negatively functional diversity. Our results suggest that larger islands accumulate functionally and phylogenetically unique species. Further, results for functional diversity pointed towards potential area–heterogeneity trade‐offs, with these trade‐offs likely resulting from increased interspecific competition favoring a specific set of trait values (of stronger competitors), particularly on smaller islands. Together, these results demonstrate that going beyond taxonomic diversity contributes to identifying underlying processes shaping diversity–area relationships.